Sensitive and rapid determination of amantadine without derivatization in human plasma by LC-MS/MS for a bioequivalence study - Abhaysingh Bhadoriya; Shivprakash Rathnam; Bhavesh Dasandi; Dharmesh Parmar; Mallika Sanyal; Pranav S. Shrivastav (Elsevier, 2018)
A highly sensitive, rapid and rugged liquid chromatography-tandem mass spectrometry (LC-ESI-MS/MS) method was developed for reliable estimation of amantadine (AMD), an antiviral drug in human plasma. The analyte and internal standard (IS), amantadine-d6 (AMD-d6), were extracted from 200 µL plasma by solid phase extraction on Phenomenex Strata-X-C 33 µ cartridges. Chromatography was performed on Synergi™ Hydro-RP C18 (150 mm × 4.6 mm, 4 µm) analytical column using a mixture of acetonitrile and 10 mM ammonium formate, pH 3.0 (80:20, v/v) as the mobile phase. Detection and quantitation was done by multiple reaction monitoring in the positive ionization mode for AMD (m/z 152.1 → 135.1) and IS (m/z 158.0 → 141.1) on a triple quadrupole mass spectrometer. The assay was linear in the concentration range of 0.50-500 ng/mL with correlation coefficient (r2) ≥ 0.9969. The limit of detection of the method was 0.18 ng/mL. The intra-batch and inter-batch precisions were ≤ 5.42% and the accuracy varied from 98.47% to 105.72%. The extraction recovery of amantadine was precise and quantitative in the range of 97.89%-100.28%. IS-normalized matrix factors for amantadine varied from 0.981 to 1.012. The stability of AMD in whole blood and plasma was evaluated under different conditions. The developed method was successfully applied for a bioequivalence study with 100 mg of AMD in 32 healthy volunteers. The reproducibility of the assay was determined by reanalysis of 134 subject samples. Keywords: Amantadine, Amantadine-d6, LC-ESI-MS/MS, Sensitive, Bioequivalence study, Human plasma